Hubungan Relationship Work dengan Motivasi Perawat dalam Melaksanakan Asuhan Keperawatan di Ruang Rawat Inap dan IGD RSUD Kalideres Jakarta - Fina Alfya Syahri (2020)
Motivation becomes an important part that nurses need to have a passion in implementing nursing care. A good Relationship Work is able to make nursing care more optimal. The purpose of this research is to know relationship Work relationships with the motivation of nurses in inpatient room and IGD Hospital in Kalideres Jakarta. The design of the Cross Sectional research with the Chi-Square and test used a Total Sampling of 35 nurses at the Kalideres Hospital in Jakarta. Relationship Work Questionnaire that has been conducted a validity test of 101 statements with a range r = 0.295-0.697. There is no relationship between relationship Work with the motivation of nurses in the hospitalisation Hospital Kalideres Jakarta p = 0,600 (P < 0.05) and CI 95%. The motivation of nursing in the implementation of nursing care should always be kept, nurses are given appreciation every nursing care, and Relationship Work that must be established harmoniously and in accordance with nursing care. Keyword : Motivation, Nurse, Relationship Work.